GE_GERICHTE C/13872/2016 vom 24. April 2018 - GE Cour de justice (2018)
ACTION EN RESPONSABILITÉ ; AVOCAT ; INTERRUPTION DU DÉLAI ; PRESCRIPTION ; DÉCISION DE RENVOI | CO.398.al2; CO.127; LCR.83; aCP.125.al1